2008
DOI: 10.1080/08897070802418451
|View full text |Cite
|
Sign up to set email alerts
|

Drug Exposure Opportunities and Use Patterns among College Students: Results of a Longitudinal Prospective Cohort Study

Abstract: Underage drinking and drug use among college students are major public health concerns, yet few studies have examined these behaviors and their associated risk factors and consequences prospectively. This paper describes the sampling and recruitment methods of a longitudinal study of 1,253 college students at a large, mid-Atlantic university. Incoming first-year students were screened during the unique window between high school and college in order to oversample drug users for longitudinal follow-up. Intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(189 citation statements)
references
References 52 publications
8
179
0
2
Order By: Relevance
“…Previous studies indicate that individuals who are highsensation seekers tend to be drawn to high-risk activities, including the use of alcohol and illicit drugs. [19][20][21][22][23]27,[24][25][26] Previous research suggests that both CaffAlc 14,43-45 and sensation seeking [46][47][48][49] predict the likelihood of experiencing adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that individuals who are highsensation seekers tend to be drawn to high-risk activities, including the use of alcohol and illicit drugs. [19][20][21][22][23]27,[24][25][26] Previous research suggests that both CaffAlc 14,43-45 and sensation seeking [46][47][48][49] predict the likelihood of experiencing adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies indicate that individuals who are high-sensation seekers tend to be drawn to high-risk activities, including the use of alcohol and illicit drugs. [19][20][21][22][23][24][25][26][27] High-sensation seekers may have an increased susceptibility to the subjective rewarding effects of alcohol. 28 Among college students, higher levels of sensation seeking have been linked to binge drinking.…”
Section: Introductionmentioning
confidence: 99%
“…First, high-school adolescents were simply more likely to be offered cannabis. Indeed, past research suggests that drug use opportunities become more common with age: for example, Arria et al (2008) reported that more than 80% of college freshmen have been offered cannabis and 50% of those have had such an experience by the age of 16.…”
Section: Cannabis Offersmentioning
confidence: 99%
“…For example, it is possible that these risk processes would operate differently among much older youth (Arria et al, 2008) or urban youth where access to cannabis may be easier. Next, we could not fully explore complex causal or temporal processes (Kraemer et al, 2001), nor could we fully clarify social and/or psychological mechanisms linking adolescent characteristics and cannabis offers: our results are consistent with several plausible explanations, but to which extent each of those possibilities played a role cannot be fully ascertained from these crosssectional data primarily because we could not rule out self-selection.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Bylund et al [28] tended to underestimate student work schedule, stress and substance use and overestimate their child's self-reports of general health. College/university health clinics may Source: Arria et al [30], Source legend: Graphed lines depict the weighted cumulative percent of all students who ever had the opportunity to try a substance by each age, as of the sophomore year of college. Circles on the graph indicate the age by which 50% of all students who were ever exposed to the substance had experienced their first opportunity.…”
Section: Employmentmentioning
confidence: 99%